2017
DOI: 10.2147/ijnrd.s126534
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in elderly intensive care patients from a developing country: clinical features and outcome

Abstract: Aim:The elderly are at high risk of acute kidney injury (AKI) because of structural and functional degeneration over time and with the aging of the population, the demand for intensive care unit (ICU) admission for older patients has risen recently. However, data from developing countries are scarce. This study aimed to describe the incidence of AKI in elderly patients admitted to ICU from a developing country, to determine the most frequent etiologies for renal impairment and identify its risk factors and out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
1
11
0
1
Order By: Relevance
“…Furthermore, elderly individuals are susceptible to severe infection and are therefore more likely to develop septic acute tubular necrosis (ATN) and experience mortality [3]. Indeed, infection and septic ATN were the leading etiologies of ICU admission and AKI in the present study, which is consistent with the trends in previous studies [8,14,[24][25][26].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, elderly individuals are susceptible to severe infection and are therefore more likely to develop septic acute tubular necrosis (ATN) and experience mortality [3]. Indeed, infection and septic ATN were the leading etiologies of ICU admission and AKI in the present study, which is consistent with the trends in previous studies [8,14,[24][25][26].…”
Section: Discussionsupporting
confidence: 91%
“…is can be attributed to comorbidities, increased severity of acute illnesses, polypharmacy, need for invasive procedures, and age-dependent changes in this population [5][6][7]. Majority of the studies including elderly patients have revealed that the elderly with AKI show higher mortality than those without AKI [8][9][10]. Similar findings have also been reported in other age groups [11].…”
Section: Introductionmentioning
confidence: 59%
“…Luo et al 35 performed prospective analysis of a database from Beijing (China), with more than three CONTINUATION thousand adult patients, and observed that AKI patients identified by KDIGO criteria already had worse baseline renal function in comparison with those without AKI. In this same sense, Yokota et al 24 in a prospective study with critically ill elderly patients verified that AKI patients presented worse baseline serum creatinine. Worse baseline renal function also was an AKI risk factor in the study performed by Wang et al 36 In others studies, 12,37-39 patients with AKI during ICU stay are the ones with higher serum creatinine at ICU admission, and in the studies performed by Podoll et al 38 and Peres et al 12 it was also associated with a higher risk for mortality.…”
Section: Discussionmentioning
confidence: 76%
“…However, other studies have shown that morbidity and mortality are especially high among individuals older than 60, and the risk increases linearly with age, as well as the chance of needing RRT, which further increases the mortality rate of patients. 1,2,14,17,24 Almost all studies listed in Table 1 present diabetes mellitus and systemic arterial hypertension as the chronic diseases that are the most prevalent risk factors in critically ill adults with AKI. Moreover, these are also the chronic conditions that frequently increase morbidity and mortality for AKI in critically ill patients who are septic, 11,16,25 with fluid overload, 2,9,26 making use of nephrotoxic drugs 16 or who have undergone major surgeries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation